The tropical Pacific Oceanscape: Current issues, solutions and future possibilities. (May 2021) - Devlin, Michelle J.; Lyons, Brett P.; Johnson, Johanna E.; Hills, Jeremy M.
Abstract: Marine ecosystems across the world's largest ocean – the Pacific Ocean – are being increasingly affected by stressors such as pollution, overfishing, ocean acidification, coastal development and warming events coupled with rising sea levels and increasing frequency of extreme weather. These anthropogenic-driven stressors, which operate cumulatively at varying spatial and temporal scales, are leading to ongoing and pervasive degradation of many marine ecosystems in the Pacific Island region. The effects of global warming and ocean acidification threaten much of the region and impact on the socio-cultural, environmental, economic and human health components of many Pacific Island nations. Simultaneously, resilience to climate change is being reduced as systems are overburdened by other stressors, such as marine and land-based pollution and unsustainable fishing. Consequently, it is important to understand the vulnerability of this region to future environmental scenarios and determine to what extent management actions can help protect, and rebuild ecosystem resilience and maintain ecosystem service provision. This Special Issue of papers explores many of these pressures through case studies across the Pacific Island region, and the impacts of individual and cumulative pressures on the condition, resilience and survival of ecosystems and the communities that depend on them. The papers represent original work from across the tropical Pacific oceanscape, an area that includes 22 Pacific Island countries and territories plus Hawaii and the Philippines. The 39 papers within provide insights on anthropogenic pressures and habitat responses at local, national, and regional scales. The themes range from coastal water quality and human health, assessment of status and trends for marine habitats (e.g. seagrass and coral reefs), and the interaction of local pressures (pollution, overfishing) with increasing temperatures and climate variability. Studies within the Special Issue highlight how local actions, monitoring, tourism values, management, policy and incentives can encourage adaptation to anthropogenic impacts. Conclusions identify possible solutions to support sustainable and harmonious environment and social systems in the unique Pacific Island oceanscape.